Мiсце теоретичної пiдготовки учнiв середнiх класiв на уроках фiзичної культури = Garden of theoretical preparation of students competing were the lessons physical culture - Kudryavtsev, A. I.; Gorchak, V. V.; Nikolenko, O. I. (Journal of Education, Health and Sport, 2016)
Kudryavtsev A. I., Gorchak V. V., Nikolenko O. I. Мiсце теоретичної пiдготовки учнiв середнiх класiв на уроках фiзичної культури = Garden of theoretical preparation of students competing were the lessons physical culture. Journal of Education, Health and Sport. 2016;6(12):655-665. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.221338 http://ojs.ukw.edu.pl/index.php/johs/article/view/4109 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 25.12.2016. МIСЦЕ ТЕОРЕТИЧНОЇ ПIДГОТОВКИ УЧНIВ СЕРЕДНIХ КЛАСIВ НА УРОКАХ ФIЗИЧНОЇ КУЛЬТУРИ Кудрявцев А. І., Горчак В. В., Нiколенко О. I. Національний університет водного господарства та природокористування, м. Рівне, Україна Garden of theoretical preparation of students competing were the lessons physical culture Kudryavtsev A. I., Gorchak V. V., Nikolenko O. I. National University of water management and nature resources use, Rivne, Ukraine Анотація. Метою роботи є розробка та експериментальна перевiрка системи тестового контролю i оцінки якостi знань з дисциплiни «Фiзична культура» для пiдвищення ефективностi теоретичних знань учнiв середнiх класiв. Нами вивчалась ефективнiсть створеної системи. Виявлено, що теоретичнi знання учнiв з дисциплiни «Фiзична культура» знаходяться на досить невисокому рiвнi та потребують подальшого поглиблення й заохочення дiтей до їх вивчення, що в бiльшiй мiрi вiдповiдає дiйсностi. Тому апробовану систему тестування можна вважати ефективною та такою, що дає достовiрну iнформацiю. Ключовi слова. Фiзична культура, фiзичне виховання, теоретичнi знання учнiв, оцiнка якостi знань, система тестового контролю. Abstract. The aim is to develop and pilot test system test control and evaluation of the quality of knowledge in the discipline "Physical Culture" to improve theoretical knowledge of secondary school. We studied the effectiveness of the established system. Found that students with theoretical knowledge of the subject "Physical Culture" are at quite a high level and not require further deepening and encouraging children to their study, which to a large extent true. So the system of testing can be considered effective and one that gives reliable information. Key words. Physical education, physical education, theoretical knowledge of students' knowledge assessment system test control. Аннотация. Целью работы является разработка и экспериментальная проверка системы тестового контроля и оценки качества знаний по дисциплине «Физическая культура» для повышения эффективности теоретических знаний учеников средних классов. Нами изучалась эффективность созданной системы. Выявлено, что теоретические знания учащихся по дисциплине «Физическая культура» находятся на весьма не высоком уровне и требуют дальнейшего углубления и поощрения детей к их изучению, что в большей степени соответствует действительности. Поэтому апробированную систему тестирования можно считать эффективной и дающей достоверную информацию. Ключевые слова. Физическая культура, физическое воспитание, теоретические знания учеников, оценка качества знаний, система тестового контроля.